2006
DOI: 10.1016/j.exer.2006.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome-dependent regulation of signal transduction in retinal pigment epithelial cells

Abstract: As in many other types of cells, retinal pigment epithelial (RPE) cells have an active ubiquitineproteasome pathway (UPP). However, the function of the UPP in RPE remains to be elucidated. The objective of this study is to determine the role of the UPP in controlling the levels and activities of transcription factors hypoxia-inducible factor (HIF) and NF-kB. We inhibited the UPP with proteasome-specific inhibitors and determined the activation of HIF and NF-kB as well as the expression and secretion of pro-ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 66 publications
5
35
0
1
Order By: Relevance
“…The in vivo effects were not seen when MG132 was injected at day 4 after laser, suggesting that timing of target inhibition is critical (results not shown). Restoration of VEGF-A levels in ␣B-crystallin Ϫ/Ϫ retinas and cells were only partial, which is consistent with the report by Fernandes et al, 36 who found that increases in RPE VEGF-A levels after proteasomal inhibition may be mediated by competing effects on HIF-1␣. The effects of proteasomal inhibition on angiogenesis in vivo are even more complex; inhibitors of the proteasome also can inhibit angiogenesis through regulation of multiple targets of the proteasome, including apoptosis mediators 37 and components of the inflammatory response, 38 and in models of tumor angiogenesis, MG132 has been reported to inhibit VEGF-A production.…”
Section: Discussionsupporting
confidence: 81%
“…The in vivo effects were not seen when MG132 was injected at day 4 after laser, suggesting that timing of target inhibition is critical (results not shown). Restoration of VEGF-A levels in ␣B-crystallin Ϫ/Ϫ retinas and cells were only partial, which is consistent with the report by Fernandes et al, 36 who found that increases in RPE VEGF-A levels after proteasomal inhibition may be mediated by competing effects on HIF-1␣. The effects of proteasomal inhibition on angiogenesis in vivo are even more complex; inhibitors of the proteasome also can inhibit angiogenesis through regulation of multiple targets of the proteasome, including apoptosis mediators 37 and components of the inflammatory response, 38 and in models of tumor angiogenesis, MG132 has been reported to inhibit VEGF-A production.…”
Section: Discussionsupporting
confidence: 81%
“…Oxidative inactivation of the proteasome and the subsequent alterations in several signaling pathways, such as NF-B and p38 MAPK, are plausible mechanisms that underlie the oxidative stress-induced upregulation of IL-8, one of the most potent proinflammatory and proangiogenic chemokines. Given the function of the UPP in regulating IL-8, vascular endothelial growth factor and MCP-1 in RPE cells (27) and the roles of these chemokines and growth factor in the pathogenesis of AMD (38, 39, 86), impairment of the UPP in RPE could significantly contribute to the development of AMD. Thus, protecting the UPP from oxidative inactivation may become a valid therapeutic strategy for prevention of AMD and other age-and inflammation-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Real Time RT-PCR-Total RNA extraction from ARPE-19 cells and real time RT-PCR analysis were performed as described (27). For IL-8, the forward primer was: 5Ј-AAAC-CACCGGAAGGAACCAT-3Ј and the reverse primer was: 5Ј-CCTTCACACAGAGCTGCAGAAA-3Ј.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 However, recent studies have revealed the importance of the HIF-independent, PGC-1/ERR- Figure 1. Definition of intense physiological light for mice.…”
Section: Vegf Upregulation In Rpe Cells Treated With Os Is Mediated Bmentioning
confidence: 99%